2015
DOI: 10.1177/0018726714556156
|View full text |Cite
|
Sign up to set email alerts
|

Reflexivity in practice: Tools and conditions for developing organizational authorship

Abstract: In this paper, we build on the results of a participatory action research project in healthcare to discuss a number of methods that can strengthen the link between reflexive work and authoring in organizational contexts. We argue that from an organizational point of view, the challenge is to devise new ways to configure (and consider) people as the authors of their work. This means assuming responsibility for, and constructively contributing to, the goals of the organizations to which they belong. Combining in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 58 publications
0
77
0
6
Order By: Relevance
“…As Gorli et al (2015) put it, there is a switch from ongoing authorship (the construction of the context through one's practices) to a reflexive focus on authoring (understanding oneself as a constructor of the organization and changing how one practices in response to that). As such, it may not be about transforming oneself to resemble a positive role model, but instead be about avoiding becoming a negative one.…”
Section: Reconfiguringmentioning
confidence: 99%
“…As Gorli et al (2015) put it, there is a switch from ongoing authorship (the construction of the context through one's practices) to a reflexive focus on authoring (understanding oneself as a constructor of the organization and changing how one practices in response to that). As such, it may not be about transforming oneself to resemble a positive role model, but instead be about avoiding becoming a negative one.…”
Section: Reconfiguringmentioning
confidence: 99%
“…Synthesising Beech's notion with Schatzki's underlines the significance and importance of contestation and conflict during episodes of design evaluation practice. The study has shown that analysing such 'arresting moments' invokes practical reflexivity (Gorli et al, 2015), not only at a personal level, but also between the stakeholders. Design evaluation practices are thus not only based on shared understandings, rather a more nuanced view, which appreciates the reality of such practices that include the unpredictable presence of such conflicts.…”
Section: Invoking Practical Reflexivity and The Role Of "Arresting Momentioning
confidence: 98%
“…The necessary condition for this is the collaboration with practitioners working within the organization and "the challenge is thus to devise new ways of making (and considering) people as the authors of their work. The expectation is that this will enable people to shoulder and contribute to the goals of the organizations they belong to" (Gorli et al 2015). In fact, the collective engagement of researchers and participants in reflexivity (Cunliffe 2003) can help to bring to the surface the knowledge embedded in practicing and transform it into actionable knowledge (Argyris and Schon 1978).…”
Section: Implications For Experimenting In Trainingmentioning
confidence: 99%